Efeitos da Sulpirida e do Haloperidol na expressão e extinção do medo condicionado à luz e ao contexto em ratos - Vita, Vivian Maria de (2019)
Evidence suggests that dopamine (DA) is one of the most active neuromodulators in mechanisms underlying states of fear and anxiety. More specifically, during the exposure to aversive conditioned stimuli, there is an increase in the release of DA from the ventral tegmental area (VTA) to structures such as the basolateral amygdala complex (BLA) and nucleus accumbens. Furthermore, results point to a greater involvement of the D2-type DA receptors in conditioned fear expression, since both the administration of the D2 agonist, quinpirole, and the D2 antagonist, sulpiride, cause a significant reduction of conditioned freezing with the action of the drugs in VTA and BLA receptors, respectively. Thus, the general objective of this study is to broaden the evaluation of the effects of D2 receptor blockade in rats on the expression and extinction of conditioned fear. We aim to replicate the previous findings regarding the effects of sulpiride on decreasing the expression of conditioned fear, to test the hypothesis that haloperidol - a D2 antagonist widely used in clinical settings to control symptoms of the acute phase of schizophrenia - would present similar effects to sulpiride, and to extend the characterization of the involvement of DA in conditioned fear by evaluating the effects of these two drugs on extinction processes. For this, 146 male Wistar rats weighing approximately 300 g were used. The animals were trained to the context or to the light (conditioned stimulus) using footshocks as an unconditioned aversive stimulus. After 24 hours, the rats received intraperitoneal administration of drug (sulpiride or haloperidol) or vehicle and they were exposed to the context or the light for evaluation of the freezing response (test). After another 24 hours, the same animals were submitted to a retest, to evaluate the retention of extinction. For control of possible adverse motor effects, catalepsy and open field tests were performed. As expected, sulpiride decreased the freezing response in the test for both context and light conditioned fear. No motor impairment was observed in the catalepsy or open field tests with sulpiride administration. The administration of haloperidol did not cause significant effects on the expression or extinction of the context or light conditioned fear, although a clear tendency to decrease the freezing in the test was observed. On the other hand, in general, haloperidol induced catalepsy and impaired motor activity in the open field. Therefore, we reproduce the previous findings for sulpiride in decreasing freezing in the conditioned fear test. In addition, we have shown similar effects for haloperidol in the test (although not statistically significant), reinforcing the idea of D2 receptor involvement in conditioned fear expression.